Central pulse load and coronary flow benefit in relation to endogenous testosterone and the Mediterranean regime in hypertensive males with erectile dysfunction. (25th November 2020) - Angelis, A; Aggeli, K; Ioakeimidis, N; Georgakopoulos, C; Zisimos, K; Raftopoulos, L; Aznaourides, K; Dimitroglou, I; Laina, A; Verveniotis, A; Krommydas, A; Terentes-Printzios, D; et al.
Abstract: Background: Central pulse pressure (cPP) is an important parameter of target organ damage (TOD) in essential hypertension. Coronary flow reserve (CFR) displays the ability of both macro and microcirculation to augment flow to the myocardium while endogenous total testosterone (TT) exhibits vasodilator effects. The Mediterranean diet (Med-diet) benefits cardiovascular health and erectile dysfunction (ED) often coexists with the decline of endogenous testosterone in the aging male population. Purpose: To investigate the possible benefits of the Med-diet in central PP, CFR and erectile ability in relation to endogenous TT in the primary hypertensive population with ED. Methods: 247 male hypertensive patients (mean age 57 yo) with ED enrolled the study. Significant coronary artery disease was formerly excluded by a dobutamine stess echo test. We measured the CFR of the left anterior descending artery by performing an adenosine protocol (maximum dose 140 μg/kg/min over 6 minutes). Measurements by the PW Doppler were achieved at the middle/distal LAD segment under the guidance of color Doppler flow mapping. CFR was validated as ratio between peak diastolic flow velocity following drug infusion and rest. Ratios ≥2 are considered as non-ischemic response and higher values indicate microvascular coronary integrity. TT was measured in all patients on blood samples taken before 09:00 am. ED severity and adherence to the Med-diet were assessed by the SHIM-5 (range: 0–25) and the Med-diet (range: 0–55) scores. Higher values indicate a better erectile ability and Med-diet compliance respectively. Finally, cPP and augmentation index (AIx) were estimated as parameters of central hemodynamic load and wave reflection amplification respectively (sphygmocor device). Results: In bivariate analysis Med-diet was favorably related to CFR (p=0.24, r=0.48), TT (p=0.01, r=0.57) and the SHIM-5 score (p=0.01, r=0.45). On the contrary, it was negatively related to cPP (p=0.15, r=−0.60) and AIx (p=0.31, r=−0.45). CFR was strongly related to TT (p=0.001, r=0.8) and the SHIM-5 score (p=0.01, r=0.41). By multiple linear regression analysis the relation of CFR, SHIM-5 and Med-diet score remained significant after adjustment for age, BMI, systolic arterial blood pressure and smoking habits. We further subdivide our population according to the mean Med-diet value (26) into high and low Med-diet adherence groups. Only in the group with the greater Med-diet adherence (n=153, 62%) there were still positive relation with the CFR, TT and SHIM-5 score as well as negative correlation to cPP and AIx (p=0.04). Conclusion: In essential hypertensive males with erectile dysfunction the Med-diet regime lessens central pulse pressure while enhancing coronary flow, testosterone levels and so peripheral vascular physiology. We strongly recommend this dietary pattern as a life-style option and strategic component of holistic therapeutic approach. Funding Acknowledgement: Type of funding source: None